Oops! Its happened again! Evidence of the continuing abuse of older people in care homes. Issue 1 (12th February 2018) - Moore, Steve
Abstract : Purpose: The purpose of this paper is to present findings from an empirical research project designed to enhance knowledge of the current extent and nature of abuse in contemporary care homes for older people. Design/methodology/approach: A self-completion, postal questionnaire was used to elicit both numerical and textual data that was subsequently subjected to both quantitative and qualitative analysis. The questionnaire was distributed to newly appointed care staff in six participating care homes providing care to older people to determine the nature of any abuse they may have witnessed in the homes in which they had previously worked. Findings: A significant proportion of respondents described instances of predominantly psychological and physical abuse and neglect. Research limitations/implications: Though the research draws upon the experiences of only 194 anonymous questionnaire respondents, of whom 140 had witnessed abuse; data suggest that abuse continues to occur in some care homes for older people. Originality/value: The research has revealed staffs' recent experiences of a range of abusive acts and practices. Findings suggest that changes are required to current methods of external scrutiny and investigation of practices in care homes.